2022
DOI: 10.5298/1081-5937-50.04.05
|View full text |Cite
|
Sign up to set email alerts
|

RESEARCH ARTICLE: Heart Rate Variability Biofeedback: Managing Disorders of Gut-Brain Interaction by Improving Autonomic Homeostasis

Abstract: Disorders of gut-brain interaction, previously called functional gastrointestinal disorders, are prevalent, disabling, expensive, and difficult to treat. In this review, I trace the available scientific knowledge on the pathophysiology of these disorders and describe how the proposed pathways are integrated into treatment approaches. A novel treatment approach, heart rate variability biofeedback (HRVB), is described, and outcome literature is reviewed. It is concluded that an approach such as HRVB offers benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…38,39 The work is also consistent with advances in the field of medicine, where a range of surgically implanted devices-and transcutaneous devices in the more recent past-were developed to modulate spinal cord afferents or the vagal nerve itself in cases of intractible pain, refractory epilepsy, or depression. 37 Likewise, recent advances in neuroscience have confirmed that breathing interventions used for upregulating vagal function and for pro-moting states of well-being [54][55][56] rest on a solid evidence base. That is, though the history and effective use within Eastern traditions date back thousands of years, it is only very recently that the neuroanatomy, including the close anatomical proximity of the respiratory rhythm generator and vagal nuclei in the brain stem-which facilitates the functional coupling between them-has been clearly delineated.…”
Section: Stephen Porges Phdmentioning
confidence: 99%
“…38,39 The work is also consistent with advances in the field of medicine, where a range of surgically implanted devices-and transcutaneous devices in the more recent past-were developed to modulate spinal cord afferents or the vagal nerve itself in cases of intractible pain, refractory epilepsy, or depression. 37 Likewise, recent advances in neuroscience have confirmed that breathing interventions used for upregulating vagal function and for pro-moting states of well-being [54][55][56] rest on a solid evidence base. That is, though the history and effective use within Eastern traditions date back thousands of years, it is only very recently that the neuroanatomy, including the close anatomical proximity of the respiratory rhythm generator and vagal nuclei in the brain stem-which facilitates the functional coupling between them-has been clearly delineated.…”
Section: Stephen Porges Phdmentioning
confidence: 99%
“…Reviews and meta-analyses have found that cognitive behavioral therapy (CBT), hypnotherapy, mindfulness-based approaches, and relaxation therapies, improve symptoms in pediatric patients (Abbott et al, 2017; Buffone & Goldman, 2021; Laird et al, 2017). These treatment modalities may assist in teaching patients to better manage their responses or reactions to their symptoms (Gevirtz, 2022). Gains in patient outcomes typically include decreases in pain, frequency of symptoms, anxiety, and depression as well as increases in daily functioning (Abbott et al, 2017; Laird et al, 2017).…”
Section: Pathophysiology Of Dgbimentioning
confidence: 99%
“…CBT may indirectly target the ANS, particularly the parasympathetic nervous system, by modifying maladaptive cognitions regarding pain, its associated behavioral responses, and by promoting pain coping mechanisms (Gevirtz, 2022). Mindfulness-based stress reduction (MBSR) may result in decreased autonomic arousal through the nonjudgmental awareness of thoughts and emotions and the associated reduction in reactivity to pain (Gevirtz, 2022). As such, MBSR has been associated with significant improvements in GI symptoms in patients with IBS (Naliboff et al, 2020).…”
Section: Pathophysiology Of Dgbimentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has supported the research hypothesis that a slow breathing technique, HRVB, which uses beat-by-beat heart rate feedback, can aid in depression reduction, faster extinction, and better autonomic balance. This type of biofeedback was developed by Paul Lehrer and colleagues (Gevirtz, 2000(Gevirtz, , 2013Gevirtz & Lehrer, 2003;Lehrer, Smetankin, & Potapova, 2000;Lehrer et al, 2003Lehrer et al, , 2004Lehrer et al, , 2006Lehrer, Vaschillo, & Vaschillo, 2000).…”
Section: The Role Of the Vagus Recovery In The Treatment Of Trauma An...mentioning
confidence: 99%